Post-harvest loss in Mozambique: Estimating maize loss in Manica and Zambezia provinces - Delgado, Luciana; Laborde Debucquet, David; Piñeiro, Valeria (Food and Agricultural Organization of the United Nations, 2021)
In Mozambique, food security remains a key issue and the country suffers perennial food shortages, especially in the provinces of Manica,Tete, Sofala, Zambezia, Maputo and Gaza. Weaknesses in post-harvest systems, which contribute to both a lower supply and higher food prices (due to post-harvest losses) are key reasons behind these food shortages. Currently, none of the post-harvest losses programmes conducted in Mozambique provides loss estimates along the entire value chain for a given commodity. In this report, we quantify losses across the value chain in maize, which is a key staple food in Mozambique, in the provinces of Manica and Zambezia. The study, carried out by the International Food Research Institute (IFPRI) in collaboration with the Agrifood Economics Division (ESA) at FAO, sheds light on understanding the magnitude, nature and consequences of food losses across the maize value chain in selected regions in Mozambique. In particular, the methodology used in this report allows to accurately measure food losses and identify in which segment of the value chain these food losses occur and the causes of the losses.